La gestion des archives audiovisuelles à l'Institut national de l'audiovisuel - Dumont, J. (Documentaliste, 1978)

Une expérience de dépôt et de classement des archives consulaires à Colmar - Kammerer, Odile (Gazette des archives, 1978)
An experience of deposit and ordening of the archives of the «Chambre de Commerce » of Colmar at the «Archives départementales » of Haut-Rhin. How the deposit was envisaged and realised ; what the cooperation was between the personnel of the Archives and the personnel of the Chambre de Commerce ; procedures and difficultes of arrangement and inventorying ; summary of the repertory.

Les archives d'entreprises en U.R.S.S - Romanow, W. B. (Comité international des archives (Bulletin), 1978)